Identification of the Spinal Expression Profile of Non-coding RNAs Involved in Neuropathic Pain Following Spared Nerve Injury by Sequence Analysis - Zhou, Jun; Xiong, Qingming; Chen, Hongtao; Yang, Chengxiang; Fan, Youling (Frontiers in Molecular Neuroscience, 2017)
Neuropathic pain (NP) is caused by damage to the n r ous system, resulting in aberrant pain, which is associated with gene expression cha ges in the se so y pathway. How r, the molecular mechanisms are not fully understood. A Non-Coding RNA (ncRNA) is an RNA molecule that is not t anslat d into a protein. NcRNAs are involved in many cellular processes and mutations or imbalances of repertoire in which within the body can cause a variety of diseases. Although ncRNAs have recently been shown to play a role in NP pathoge esis, the specific influences of ncRNAs in NP are remain largely unknown. In this study, sequencing analysis was performed to i vestigated the expression patterns of ncRNAs in the spinal cord following spared nerve injury-induced NP. A total of 134 lncRNAs, 12 miRNAs, 188 circRNAs and 1066 mRNAs were found to be significantly regulated at 14 days after SNI surgery. Then, quantitative real-time PCR was used to validate the expression of selected lncRNAs, miRNAs, circRNAs and mRNAs. Bioinformatics tools and databases were employed to explore the potential ncRNA functions and relations. This is the first study to comprehensively identify regulated ncRNAs of spinal cord and to demonstrate the involvement of different ncRNA expression patterns in the spinal cord of NP pathogenesis. This information will enable further research on the pathogenesis of NP and facilitate the development of novel NP therapeutics targeting ncRNAs.